CORAK ESTETIKA PERTUNJUKAN WAYANG GAGRAG BANYUMAS SAJIAN PANDU NUR PRASTIYO LAKON SEMAR BANGUN KAYANGAN - salim (Canthing, 2025)
This research focuses on the study of popular aesthetics in the Banyumasan style shadow puppet performance presented by Pandu Nur Prastiyo through the play Semar Bangun Khayangan. The formulation of the problems raised in this research include: (1) What is the structure of the Banyumasan style shadow puppet performance presented by Pandu Nur Prastiyo in the play Semar Bangun Kayangan? (2) What is the form or aesthetic pattern displayed in the 1 Vol. 11 | No. 1 | Tahun 2025 performance?" The analysis of the two problems was carried out using an aesthetic approach in the world of puppetry, especially through an understanding of the concepts of Nuksma and Mungguh. In addition, the analysis of the performance structure refers to the Banyumasan Gagrag Puppetry Path as a reference. The research findings show that the achievement of the Nuksma value can be observed through the puppeteer's ability to present a musical atmosphere such as gending beregu, trenyuh, greget, sereng, gandrung, to prenes. This nuance is built through a harmonious combination of catur (speech), sabet (movement), and karawitan (accompanying music) elements in each scene. Based on the analysis of these pakeliran elements, it can be concluded that the aesthetic pattern in the Banyumasan gagrag shadow puppet performance is known as nyopak. Keywords: Aesthetics, Shadow Puppet, Pandu Nur Prastiyo, Semar Bangun Khayangan, Banyumasan Styl